Strategic consequences of India's economic performance : essays & columns - Baru, Sanjaya (New Delhi : Academic Foundation, 2006)
In this collection of academic essays and newspapers columns, that experts and lay readers would find equally stimulating, Baru explores the business of diplomacy and the diplomacy of business in a rising India. The role of India's cultural and intellectual 'soft power' in shaping global perceptions of India are examined. The book offers a panoramic view of the geopolitics and geo-economics of India's recent rise as a free market democracy---Book Jacket.
Includes bibliographical references (p. [465]-468) and index.
rpm 16/09/16
Loans
Keywords: National security -- Economic aspects -- India; India -- Foreign economic relations; India -- Economic policy -- 1991-; India